A global view on digital legal deposit: what could be learned?. Issue 1 (April 2022) - Neshat, Narges; Ghasemi, Rahim
Aim: Procedures for legal deposit of the print material are well established and widely practiced. Such procedures, however, are not necessarily applicable to the digital environment, mainly because bibliographic specifications of print material do not match those of digital objects and digital environment. The history of legal deposit of publications in Iran goes back to 1906. Since then, the press, publishers, public and private institutions are required to deposit one or more copies of their published material to the National Library of Iran (NLIR). However, reports have always indicated incomplete deposit or lack of coherent and comprehensive policies, especially with regard to digital resources. The present study aims to propose a framework for NLIR by comparing several national libraries. Methodology: This research examined the policies and practices of 10 large national libraries that according to the World atlas (2018) have been ranked the highest in terms of the number and variety of resources. They were the Library of Congress, the British Library, National Library and Archives of Canada (LAC), and national libraries of France, Germany, Denmark, Spain, Australia, Japan, and China. The data related to digital legal deposit implementation was collected from various sources including directories; official publications of international organizations, national legal deposit laws and regulations. Findings: A global trend towards legal deposit to cover digital publications and preservation of comprehensive national archives is developing. In Iran, there was no mechanisms for identification, selection and deposit of digital materials either do not exist or are inappropriate for some types of publications. Conclusion: National libraries and other libraries are at the forefront of research and development in the field of legal deposit. In this research, an effort was made to design and propose a framework for depositing digital material at NLIR drawing on the policies and practices of the top 10 national libraries. The proposed framework has two parts. The first includes elements such as introduction, general principles, resources comprehensiveness, legal deposit method, the origin of publications, collaboration and partnership, and legal considerations. In the second part -the plan-areas addressed in the first part are discussed in detail.